2017
DOI: 10.1128/jvi.02076-16
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with DNA Plasmids Coding for Crimean-Congo Hemorrhagic Fever Virus Capsid and Envelope Proteins and/or Virus-Like Particles Induces Protection and Survival in Challenged Mice

Abstract: Crimean-Congo hemorrhagic fever virus (CCHFV) is a bunyavirus causing severe hemorrhagic fever disease in humans, with high mortality rates. The requirement of a high-containment laboratory and the lack of an animal model hampered the study of the immune response and protection of vaccine candidates. Using the recently developed interferon alpha receptor knockout (IFNAR−/−) mouse model, which replicates human disease, we investigated the immunogenicity and protection of two novel CCHFV vaccine candidates: a DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
119
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(123 citation statements)
references
References 35 publications
1
119
1
Order By: Relevance
“…In mouse efficacy studies using A129 mice, despite the induction of strong neutralising antibody titres, the tc-VLPs only protected 40% of animals [91]. Results with these subunit vaccine approaches therefore demonstrate that neutralisation activity is unlikely alone to be an accurate measure of protection against CCHFV infection.…”
Section: Vaccine Progressmentioning
confidence: 97%
See 3 more Smart Citations
“…In mouse efficacy studies using A129 mice, despite the induction of strong neutralising antibody titres, the tc-VLPs only protected 40% of animals [91]. Results with these subunit vaccine approaches therefore demonstrate that neutralisation activity is unlikely alone to be an accurate measure of protection against CCHFV infection.…”
Section: Vaccine Progressmentioning
confidence: 97%
“…Additionally, the use of convalescent plasma as a post-exposure prophylactic has not been particularly effective [63]. Recent vaccine studies have also indicated that the induction of neutralisation antibodies does not correspond to vaccine efficacy [91], [92]. Thus cell-mediated immunity looks likely to play a major role in developing effective protection against CCHFV.…”
Section: The Case and Need For Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a DNA vaccine against the M genome segment of CCHFV has been developed, but reports from experimental animal models indicate that it is not highly immunogenic [98] . Despite insufficient neutralizing antibody titers in mice immunized with DNA plasmids developed against virus capsid and envelope proteins, Th1 response was reported to be important in protection [99] . A vaccine developed in Turkey against the Turkey-Kelkit-06 CCHFV strain resulted in measurable levels of neutralizing antibody in the serum of infected mice after a second vaccination [100] .…”
Section: Preventionmentioning
confidence: 99%